International scientific associations of the History of Science and Technology: formation and development (part III) - Lytvynko, A. (Studies in history and philosophy of science and technology, 2021)
The activity of international organizations on the history and philosophy of science and technology is a remarkable phenomenon in the world scientific and sociocultural sphere. Such centers influence and contribute to the scientific communication of scientists from different countries and the comprehensive development of numerous aspects of the history and phylosiphy of science and technology, carry out scientific congresses. That is why the analysis of the acquired experience and the obtained results of these groups are important. The history of the formation and development, task, structure, background and directions of the activities of some international organizations in the field of history and philosophy of science and technology, including The European Philosophy of Science Association (EPSA), The International Society for the History of Philosophy of Science (HOPOS), The International Federation of Philosophical Societies (FISP) and The International council for philosophy and human sciences (ICPHS) have been shown. The European Philosophy of Science Association (EPSA) was established in 2007 to promote and advance the investigations and teaching the philosophy of science in Europe. EPSA edits the European Journal for Philosophy of Science (EJPS), which publishes articles in all areas of philosophy of science. The International Society for the History of Philosophy of Science (HOPOS) promotes serious, scholarly research on the history of the philosophy of science and gathers scholars who share an interest in promoting research on the history of the philosophy of science and related topics in the history of the natural and social sciences, logic, philosophy and mathematics. The scholarly journal HOPOS is published by University of Chicago Press. The International Federation of Philosophical Societies (FISP) is the highest nongovernmental world organization for philosophy, whose members-societies represent every country where there is significant academic philosophy. It was established in Amsterdam in 1948. FISP’s first seat was located at the the Sorbonne in Paris. FISP includes approximately one hundred members. It does not include individual members, but only «societies» in a broad sense, that is, philosophical institutions of different kinds, such as associations, societies, institutes, centres and academies at national, regional and international levels. The International council for philosophy and human sciences (ICPHS) is a non-governmental organisation within UNESCO, which federates hundreds of different learned societies in the field of philosophy, human sciences and related subjects. It was conceived as the intermediary between UNESCO on one hand, and learned societies and national academies on the other. Its aim was to extend UNESCO's action in the domain of humanistic studies.